Transcriptome and Proteome Analyses Reveal Stage-Specific DNA Damage Response in Embryos of Sturgeon (Acipenser ruthenus) - Gazo, Ievgeniia; Naraine, Ravindra; Lebeda, Ievgen; Tomčala, Aleš; Dietrich, Mariola; Franěk, Roman; Pšenička, Martin; Šindelka, Radek (International journal of molecular sciences, 2022)
DNA damage during early life stages may have a negative effect on embryo development, inducing mortality and malformations that have long-lasting effects during adult life. Therefore, in the current study, we analyzed the effect of DNA damage induced by genotoxicants (camptothecin (CPT) and olaparib) at different stages of embryo development. The survival, DNA fragmentation, transcriptome, and proteome of the endangered sturgeon Acipenser ruthenus were analyzed. Sturgeons are non-model fish species that can provide new insights into the DNA damage response and embryo development. The transcriptomic and proteomic patterns changed significantly after exposure to genotoxicants in a stage-dependent manner. The results of this study indicate a correlation between phenotype formation and changes in transcriptomic and proteomic profiles. CPT and olaparib downregulated oxidative phosphorylation and metabolic pathways, and upregulated pathways involved in nucleotide excision repair, base excision repair, and homologous recombination. We observed the upregulated expression of zona pellucida sperm-binding proteins in all treatment groups, as well as the upregulation of several glycolytic enzymes. The analysis of gene expression revealed several markers of DNA damage response and adaptive stress response, which could be applied in toxicological studies on fish embryos. This study is the first complex analysis of the DNA damage response in endangered sturgeons.
Keywords: transkriptom; poškození DNA; Male; embryo; omics; DNA Damage; sturgeon; proteom; Transcriptome; mužské pohlaví; fish; ryby; proteomika; Fishes; sperma; Semen; Animals; zvířata; Proteomics; Proteome; DNA damage response